Two cases of polyorchidism: case report and literature review - Tang, Jiaxiang; Liu, Qi; Zhao, Zhifei; Lu, Hongting (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the diagnosis, clinical presentation, and management of polyorchidism, aiming to enhance awareness of this rare condition.MethodsA retrospective analysis was conducted of two children diagnosed with polyorchidism at the Qingdao University Affiliated Women and Children's Hospital between December 2022 and January 2025. A comprehensive review of the relevant literature was also performed.Results(1) Case 1: A 3-year and 9-month-old male presented with a palpable mass in the right scrotum, initially diagnosed as a right-sided inguinal hernia. Preoperative ultrasound suggested the mass might be a testicle. The mass was completely excised and sent for pathological examination, which confirmed the diagnosis of polyorchidism. Case 2: A 7-year-old male presented with a reducible mass in the left scrotum for 6 months and a history of phimosis. Initial diagnosis included left-sided inguinal hernia and phimosis. Preoperative ultrasound suggested a left inguinal hernia, with bilateral testicular asymmetry. The right testicle showed increased mobility, and an echoic mass was observed in the right scrotum, indicating the possibility of polyorchidism. The patient underwent laparoscopic high ligation of bilateral hernia sacs, excision of the right scrotal mass, and circumcision. Pathology confirmed the diagnosis of polyorchidism. Both testicles of the two children could be palpated in the scrotum, with normal texture and no tenderness. Both children were cured and discharged without complications. Follow-up showed no abnormalities. (2) A summary of the clinical features and treatment of polyorchidism was compiled from both this case series and previous reports.ConclusionPolyorchidism is an extremely rare congenital anomaly of the male reproductive system. Pediatric surgeons and urologists should increase awareness of this condition to avoid misdiagnosis and delayed diagnosis.